Place Identity of Korean Restaurants in Bandung, Indonesia - Sari, Aida Faiz Mutiara; Anggrahita, Hayuning; Zulkarnaen, Alif Raya; Guswandi, Guswandi (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
Place identity is a perception that comes from social actors who have knowledge, interest, or authority in that place. Moreover, it refers to the relationship between space and its identity. It emphasizes its meaning and significance for individuals that experience it. Korean restaurant In Bandung-Indonesia is a culinary or food business that combines South Korean culture as an attraction that can become the identity of the place. Bandung Wetan Sub-District in Bandung City, Indonesia, is chosen as the case study location to determine the place identity of Korean restaurants. This study aims to determine the place identity of Korean restaurants based on visitors’ perceptions by using a qualitative approach. Data is collected from in-depth interviews, field observations, and literature studies. They are processed and analyzed descriptively and spatially using verbatim categorization, map interpretation, and data triangulation. Based on the principle of place identity and visitors’ perception, the study finds that one restaurant has a place identity with a solid South Korean cultural concept of the three Korean restaurants. While the other two restaurants have a place identity that does not carry any South Korean culture, they apply modern restaurants' concept that serves Korean food.